AN OPTIMIZED SQUARE ROOT ALGORITHM FOR IMPLEMENTATION IN FPGA HARDWARE - Tole Sutikno (Universitas Ahmad Dahlan, 2010)
This paper presents an optimized digit-by-digit calculation method to solve complicated square root calculation in hardware, as a proposed simple algorithm for implementation in field programmable gate array (FPGA). The main principle of proposed method is two-bit shifting and subtracting-multiplexing operations, in order to achieve a simpler implementation and faster calculation. The proposed algorithm has conducted to implement FPGA based unsigned 32-bit and 64-bit binary square root successfully. The results have shown that proposed method is most efficient of hardware resource compare to other methods. In addition, the strategy can be expanded to larger number easily.